2022
DOI: 10.1093/humrep/deac107.525
|View full text |Cite
|
Sign up to set email alerts
|

P-569 Reduction of gonadotropin-dosage towards the end of ovarian stimulation for IVF/ICSI improves ART-outcome in a subgroup of patients

Abstract: Study question To identify in an unselected patient population those patients, who would benefit from a gonadotropin stepdown towards the end of ovarian stimulation in IVF/ICSI-treatment Summary answer Reduction of gonadotropin-dosage during ovarian stimulation for IVF/ICSI is beneficial in FSH-stimulated patients, aged 26-30 years, and in HMG-stimulated patients, aged 36-40 years of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hassan et al, (2017) in their study suggested FSI as a novel tool for future guide of IVF cycle management for couples by the calculation of FSI by estimation of their ovarian follicles and by being an excellent and absolute criterion of good/poor ovarian reaction in IVF/ICSI phases and can be a worthy guide cycle termination *Corresponding author: dr.sadia89@hotmail.com criteria for deprived ovarian reaction (Hassan et al, 2017). ICSI is microscopic technique that aids in conception of an oocyte by injecting a solitary spermatozoon directly (Lawrenz et al, 2022). Insulin like growth factor-1 (IGF-1), 'an ovarian IGF system's member, has expected to show immediate outcomes on function of granulosa cell in human.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hassan et al, (2017) in their study suggested FSI as a novel tool for future guide of IVF cycle management for couples by the calculation of FSI by estimation of their ovarian follicles and by being an excellent and absolute criterion of good/poor ovarian reaction in IVF/ICSI phases and can be a worthy guide cycle termination *Corresponding author: dr.sadia89@hotmail.com criteria for deprived ovarian reaction (Hassan et al, 2017). ICSI is microscopic technique that aids in conception of an oocyte by injecting a solitary spermatozoon directly (Lawrenz et al, 2022). Insulin like growth factor-1 (IGF-1), 'an ovarian IGF system's member, has expected to show immediate outcomes on function of granulosa cell in human.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin like growth factor-1 (IGF-1), 'an ovarian IGF system's member, has expected to show immediate outcomes on function of granulosa cell in human. A vital function of IGF-I in controlling of human follicles and embryo's growth by regulation of the cell cycle has been noted and observed at various levels (Lawrenz et al, 2022). It has also been seen to be mediating production of estrogen and aromatase activity by the emerging follicles (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%